2012
DOI: 10.1007/s00038-012-0388-3
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and neglect of older persons in seven cities in seven countries in Europe: a cross-sectional community study

Abstract: Country of residence of older people is independent from the four assessed domains associated with AO. Life course perspectives on AO are highly needed to get better insight, and to develop and implement prevention strategies targeted at decreasing prevalence rates of AO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
57
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 29 publications
10
57
0
5
Order By: Relevance
“…Elder abuse is a worldwide health problem. Prevalence of elder abuse varies depending on the population, settings, definitions, and research methods (Table and online Figure S2) . In North and South America, the prevalence of elder abuse in this review ranges from 10% in cognitively intact older adults to 47.3% in older adults with dementia .…”
Section: Methodsmentioning
confidence: 99%
“…Elder abuse is a worldwide health problem. Prevalence of elder abuse varies depending on the population, settings, definitions, and research methods (Table and online Figure S2) . In North and South America, the prevalence of elder abuse in this review ranges from 10% in cognitively intact older adults to 47.3% in older adults with dementia .…”
Section: Methodsmentioning
confidence: 99%
“…However, in Europe, the prevalence of psychological abuse was of 6.9-35.6%; financial abuse prevalence was of 1.7 to 9.6%; and physical abuse prevalence was of 0.3-2% (20) . In the United States, verbal abuse reached 9%, financial abuse reached 3.4%, and physical abuse reached 0.2% (21) .…”
mentioning
confidence: 94%
“…Moving from perceived data to consider findings from various studies, we found mainly cases of psychological abuse, but there was also neglect and less physical violence within the domestic setting, with an overall low prevalence of elder abuse ranging 10-14%, which is the lowest (13%) among seven European countries according with the results from the ABUEL study (Lindert et al, 2013). It is noteworthy that in Italy a large proportion of the abusive episodes often remained unrecognized (especially in case of verbal abuse).…”
Section: Main Findingsmentioning
confidence: 61%
“…A further cross-national research project was ABUEL (Elder ABUse): A multinational prevalence survey (Soares et al, 2010;Melchiorre, Di Rosa et al, 2012;Lindert et al, 2013), which had the objectives of providing data on the extent and nature of elder abuse. This study was financed in the research program area of the European Agency for Public Health (EAHC) and seven urban European centers took part.…”
Section: Cross-national Studies Based On Eu-funded Projectsmentioning
confidence: 99%